Phenotypes of synovial fluid Treg cells in checkpoint blockade-related inflammatory arthritis - He, Heyu; Zhou, Ning; Wu, Kaidi; Lin, Junhong; Zhou, Shaowei; Gu, Yuntao; Wang, Xinjia; Wang, Weidong; Mo, Lichuan; Lv, Chuanzhu (Frontiers in Oncology, 2025)
ObjectivesRegulatory T (Treg) cells may become dysregulated in checkpoint blockade-related inflammatory arthritis (CBIA), and we aimed to profile phenotypes and cytokine-secreting patterns of Tregs in CBIA.MethodsUsing a 77-protein panel, we here profiled and compared single-cell membrane proteomics of Treg cells in synovial fluid (SF) in 15 patients with active CBIA onset, 12 patients with active rheumatoid arthritis (RA), and 9 CBI-treated cancer patients with non-autoimmune inflammatory knee swelling. Microbead-sorted Treg subsets from CBIA patients underwent 32-cytokine panel secretome analysis. Peripheral blood (PB) Tregs from seven CBIA and six RA patients were similarly analyzed. Findings were correlated with the modified Clinical Disease Activity Index (mCDAI) in CBIA patients.ResultsUnsupervised clustering revealed two atypical immune-activating Treg cell clusters common to both CBIA and RA patients, in which an immunoactivating (featuring ICOS+CD134+CD137+) cluster was distinct to CBIA patients. This immunoactivating cluster was found to have a positive correlation to the mCDAI in CBIA patients. In single-cell secreting proteomics of SF-derived Treg cells in CBIA patients, we found that clusters distinct to the immunoactivating cell group featured inflammatory cytokine secretion of mainly MCP1 and MCP4, which was validated by peripheral CBIA secreting proteomics (vs. RA, which preferentially secreted CCL11/CXCL10). Other non-immunoactivating cells mainly secreted immune-modulatory cytokines of IL-10, IL-4, and TGFB1. Consistently, the MCP1/MCP4+ polysecreting cluster proportion was also positively correlated with mCDAI.ConclusionAt the single-cell proteomic level, an atypical, MCP1/MCP4+ polysecreting immunoactivating Treg cell type is found to have a strong relation to clinical disease activity of CBIA.